Solubility enhancement of crystalline nanocellulose (CNC) via dissolution of oil palm empty fruit bunches (OPEFB) - Jasmine Fong Jie Min (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Crystalline nanocellulose (CNC) has been widely recognized as an important material with high potential in contributing to a wide range of field. In this project, CNC has been produced by dissolution of oil palm empty fruit bunches (OPEFB) using ionic liquid treatment. As for the pretreatment process, alkaline pretreatment has been carried out as it removes lignin and hemicellulose effectively before proceeding with ionic liquid treatment. The solubility of CNC from OPEFB has been optimised based on its effect of temperature, process time and solvent concentration. From this project, the optimum condition to obtain the highest solubility of CNC from the dissolution of OPEFB of 31.44% has been found to be at temperature of 95 , process time of 129 minutes and solvent concentration of 95%. The CNC produced was also studied for its characterization using Fourier Transform Infrared Spectorcopy (FTIR) and Scanning Electron Microscopy (SEM) analysis. The novelity of this project is that the CNC is produced using a green and environmental friendly approach by using the ionic liquid, 1-butyl-metylimidazolium chloride, BmimCl, which is known to be a green solvent that is recyclable.